Association of Bone Mineral Density with Albuminuria and Estimated Glomerular Filtration Rate : The Dong-gu Study - Seong-Woo Choi; Hye-Yeon Kim; Hye-Ran Ahn; Young-Hoon Lee; Sun-Seog Kweon; Jin-Su Choi; Jung-Ae Rhee; Hae-Sung Nam; Seul-Ki Jeong; Kyeong-Soo Park; So-Yeon Ryu; Hye-Rim Song; et al. (Karger Publishers, 2013)
Background: Kidney dysfunction and albuminuria may be associated with BMD. However, little evidence has been reported on relationships between BMD and eGFR and albuminuria. Methods: A total of 8,992 subjects aged 50 years or older participated in a survey conducted. Participants had their lumbar spine and femoral neck BMD measured by a Lunar Prodigy bone densitometer (GE, Madison, WI). Kidney function was assessed using MDRD eGFR and diagnosis of albuminuria was based on albumin-creatinine ratio. Results: ACR was negatively associated with lumbar spine and femur neck BMD in females (lumbar spine: 1.001, 0.988, 0.974 and 0.979 g/cm2, p 2, p = 0.002), but not in males, after adjusting for covariates. Additionally, eGFR was shown to be negatively associated with lumbar spine BMD after adjusting for covariates (male: 1.181, 1.166, 1.152 and 1.149 g/cm2, p = 0.001; female: 0.997, 0.980, 0.979 and 0.982 g/cm2, p = 0.005), but demonstrated no association with femur BMD. Conclusions: ACR in females was negatively associated with lumbar spine and femur neck BMD, but not in males. eGFR was negatively associated with lumbar spine BMD in both males and females.